Promoting country ownership and inclusive growth? An assessment of Feed the Future. Issue 1 (2nd January 2017) - Tumusiime, Emmanuel; Cohen, Marc J.
ABSTRACT: This article investigates the level of country ownership and inclusivity in Feed the Future (FtF) projects in Ethiopia, Ghana, Haiti, Senegal, and Tanzania. It finds that though interventions largely align with country-defined priorities and plans, other aspects of country ownership – consultation and provision of aid through local systems – are weaker than expected. Regarding inclusion, FtF is to some extent exclusive, perhaps as an unintended consequence of alignment with national development plans that do not reasonably promote equity. Focus is mostly on productive areas and 'market-ready' smallholders. The article suggests policy actions needed to better achieve expected results.